THE ROLE OF SCHOOL METHODICAL WORK IN IMPROVING LEVEL OF CREATIVE STYLE OF PEDAGOGICAL ACTIVITY - N.V. Dudnichenko (Academy of Cognitive and Natural Sciences, 2022)
In the article methodic work at school is being discussed and the advantage of each form of methodic work is shown in connection with the.